From Evidence to Insight: AI in Digital Forensics - Premanand Narasimhan,; Dr.N.Kala, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
Cyber forensics is a rapidly evolving field that plays a critical role in investigating and mitigating cybercrime. This paper aims to provide a comprehensive introduction to the essential aspects of cyber forensics. It delves into the status of digital data, network forensics, basic log analysis, malware forensics, reverse engineering, endpoint detection, and anti-forensics techniques. With a focus on practical applications, it offers insights into frameworks, guidelines, and best practices, ensuring a robust understanding of the subject. Overview Cyber forensics is a rapidly evolving field that plays a critical role in investigating and mitigating cybercrime. This document provides an overview of key concepts, techniques, and tools used in the field of cyber forensics. It includes topics such as event log analysis, malware forensics, disk imaging, and network analysis.